(untitled) (Research, Society and Development, 2020)
To analyze and correlate the minimum level of responses to speech sounds with the auditory behavior and self-perception of quality of life of children and adolescents using hearing aids, as well as in the perception of their parents/tutors. Descriptive, cross-sectional and quantitative study. The sample consisted of 26 subjects between four and 18 years old diagnosed with hearing loss. The data were obtained from the collection of anamnesis, Ling Six Sound test and use of questionnaires, later analyzed with the Spearman Correlation Test. A negative statistical correlation was obtained between the minimum level of response to Ling Sounds to auditory behavior, absence of correlation when analyzing access to speech sounds with health-related quality of life, both considering the self-perception of children and adolescents, as in the perception of their parents/tutors. In conclusion, children and adolescents who used hearing aids had greater access to speech sounds showed better auditory behavior.